2019
DOI: 10.21037/jgo.2019.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in health-related quality of life among patients with colorectal cancer

Abstract: Background: Evidence has shown that colorectal cancer (CRC) survivors, especially women have a lower health-related quality of life (HRQOL). This study aimed to assess the QOL of CRC survivors as well as gender-related differences in the QOL of CRC patients in Northwest of Iran. Methods: This cross-sectional study was conducted in East Azarbijaban. All patients aged ≥18 years, and diagnosed with CRC regardless of its stage and plans for treatment, and also referred to teaching hospitals within a two years' tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 37 publications
(35 reference statements)
6
21
4
Order By: Relevance
“…Gender was also a factor related to the quality of life in cancer patients, as we found the emotional functioning score among females was lower than males. This share similar result to previous studies conducting on patients at different stages (Laghousi et al, 2019;Schmidt et al, 2005;West et al, 2015). Also, identical to our study, other research in Vietnam (Ngoc Thi Dang et al, 2019;Tran et al, 2019) and other countries (Jacob et al, 2019;Roick et al, 2019) have suggested that financial burden is associated with lower quality of life in cancer patients.…”
Section: Discussionsupporting
confidence: 93%
“…Gender was also a factor related to the quality of life in cancer patients, as we found the emotional functioning score among females was lower than males. This share similar result to previous studies conducting on patients at different stages (Laghousi et al, 2019;Schmidt et al, 2005;West et al, 2015). Also, identical to our study, other research in Vietnam (Ngoc Thi Dang et al, 2019;Tran et al, 2019) and other countries (Jacob et al, 2019;Roick et al, 2019) have suggested that financial burden is associated with lower quality of life in cancer patients.…”
Section: Discussionsupporting
confidence: 93%
“…Females compared to males had a higher symptom burden for nearly all recorded symptoms in our study similar to previous reported literature in oncology which also noted sex differences in symptom burden and quality of life. 7,8 Additionally, although increased co-morbidities has been previously shown to be correlated with a higher symptoms burden, 9 we did not detect a statistically significant relationship in our retrospective study and future prospective studies are needed for further investigation. Non-teaching hospital was associated with higher rates of pain and depression and although the exact reason cannot be determined from our data, clinical outcomes are known to be different among teaching versus non-teaching sites.…”
Section: -2018contrasting
confidence: 58%
“…These findings could be explained by the following reasons: (1) compared with developed areas, women with cancer have a lower priority in developing regions, which demonstrates inequality in cancer care. (2) It has been revealed that women generally have higher pain perception compared with men, which could inform health-care clinicians to make decisions in order to improve women’s quality of care [ 53 , 54 ]. In addition, for all hematologic cancers, standardized mortality and incidence rates have been detected to be higher in men.…”
Section: Discussionmentioning
confidence: 99%